2022
DOI: 10.2147/idr.s367528
|View full text |Cite
|
Sign up to set email alerts
|

Application of the ARIMA Model in Forecasting the Incidence of Tuberculosis in Anhui During COVID-19 Pandemic from 2021 to 2022

Abstract: Forecasting the seasonality and trend of pulmonary tuberculosis is important for the rational allocation of health resources. In this study, we predict the incidence of pulmonary tuberculosis by establishing the autoregressive integrated moving average (ARIMA) model and providing support for pulmonary tuberculosis prevention and control during COVID-19 pandemic. Methods: Registered tuberculosis(TB) cases from January 2013 to December 2020 in Anhui province were analysed using traditional descriptive epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Comparing our predictions with actual notified TB number from the TBIMS system in 2019 demonstrated the accuracy in our model's fit. Previous studies in other regions also used the SARIMA model to give a short-term prediction of TB epidemics with high predictive precision, which was consistent with our findings 46,47 .…”
Section: The Lower Value Of 95% CIsupporting
confidence: 92%
“…Comparing our predictions with actual notified TB number from the TBIMS system in 2019 demonstrated the accuracy in our model's fit. Previous studies in other regions also used the SARIMA model to give a short-term prediction of TB epidemics with high predictive precision, which was consistent with our findings 46,47 .…”
Section: The Lower Value Of 95% CIsupporting
confidence: 92%
“…For nonstationary time series data, the mean and variance are unstable, and they are generally converted to stationary time series by means of a differential operation. Then, stationary time series data are used to establish the ARMA mode [ 58 ]. Finally, ES was tested as the easiest forecasting technique and demonstrated that it can be used by businesses of all kinds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the ARIMA(p,d,q) model; for nonstationary time series data, the mean and variance are unstable, and such data are generally converted to a stationary time series first by means of a differential operation [58]. The ARIMA model integrates autoregressive and moving average calculations.…”
Section: Arimamentioning
confidence: 99%
“…Population gatherings, cultural programs, and religious festivals are the influencing factors that can increase TB's incidence rate during this time. It can help to monitor the trend of TB incidence and establish an accurate model to predict and control the further transmission of TB [ 6 ]. Several studies have been conducted in different geographical regions, such as India's eastern, western, northern, and southern regions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%